CONSUMER PREFERENCES ON SALAI FISH IN THE CITY OF PEKANBARU RIAU PROVINCE - Sarah, Novia; Bathara, Lamun; Warningsih, Trisla (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT                This research is about consumer preference to Salai Fish in the city of Pekanbaru Riau Province has been done in February 2018. The purpose of this research was knew consumer preference to Salai Fish purchased by consumer in Pekanbaru City.The research method be used Survey Method by conducting observations directly to the field. The sampling technique be used Accidental technique that has been done in proportion with the number of respondents as many as 60 consumers.               The result of research indicate that attribute that influence to consumer preference of Salai Fish  attribute of price, taste, texture, quality and size of fish / tail (kg). Price with a score of 104, taste with a score 152, texture with a score 161, quality with a score 166 and size of fish / tail (kg) with score 183. Consumer preferences for the Salai Fish fall on the price attribute, because the scores on the low price attribute and the lowest score were the consumer preference.  Keywords: Preferences, Consumers, Salai Fish, Pekanbaru City.